Impact of Liposomes and Ceftriaxone-Entrapped Liposomes on Skin Wound Healing in Rats - N. L. Kurilko; A. K. Kiyamov; M. A. Ivanova; E. P. Pashkov; M. T. Aleksandrov; G. M. Sorokoumova; V. I. Shvets (Антибиотики и Химиотерапия, 2020)
«Empty» liposomes and ceftriaxone (CT)-entrapped liposomes were developed. Lipids of natural origin, i. e. soybean phosphatidyl choline (PhCh) and cholesterol were used for the design. The conditions for production of the CT-entrapped liposomes were optimized to provide the maximum content of the antibiotic in the liposomes. The effect of the «empty» liposomes and the antibiotic-entrapped liposomes on healing of skin wounds was studied on rats. The wound on the skin surface of the rat back was purulent due to contamination with E.coli (109 cells/ml). The treatment with the antibiotic solution, «empty» liposomes or CT-entrapped liposomes was started in 48 hours. The use of the PhCh «empty» liposomes promoted more rapid healing of the wound vs. the control or the treatment with CT aqueous solution. The treatmen of the wound with the CT-entrapped PhCh liposomes provided 2 times more rapid healing vs. the control or the use of the CT aqueous solution.